Learning to teach in the secondary school : (Routledge, 2005)
This best-selling textbook offers a sound and practical introduction to the skills needed to gain Qualified Teacher Status, and will help you to develop those qualities that lead to good practice and a successful future in education. This 4th edition has been updated to include changes to the National Curriculum for England and Wales, as well as changes to the organization of, and curriculum for, early professional development.